Perceived maternal disapproval of friends: How mothers shape and respond to child and friend adjustment problems - Kaniušonytė, Goda; Žukauskienė, Rita; Bakaitytė, Aistė; Laursen, Brett (Frontiers in Psychology, 2022)
The present study examines relations between adjustment problems and perceptions of maternal disapproval of friends in a sample of Lithuanian public middle-school students. The participants (ages 10 to 14) were 284 children (148 boys, 136 girls) who were involved in 142 stable friendships. Each friend described their own conduct problems, emotional problems, and perceptions of maternal disapproval of friends twice during the same academic year (M = 14.4 weeks apart). Dyadic analyses replicated previous findings in that one friend’s conduct and emotional problems forecast changes in the same problems in the other friend. Greater initial problems also anticipated increases in children’s’ perceptions of disapproval of friends by their own—but not their friend’s—mother, highlighting maternal efforts to manage the relations of troubled children. These efforts met with mix success. On the one hand, maternal disapproval of friends did not result in subsequent declines in adjustment problems among their own children; to the contrary, the conduct problems of boys increased with greater maternal involvement. On the other hand, adjustment problems declined among children whose friends reported higher levels of maternal disapproval, suggesting that maternal friendship management may interfere with the spread of problems between children.